Dual RNA sequencing of a co-culture model of Pseudomonas aeruginosa and human 2D upper airway organoids - Cayetano Pleguezuelos-Manzano; Wouter A. G. Beenker; Gijs J. F. van Son; Harry Begthel; Gimano D. Amatngalim; Jeffrey M. Beekman; Hans Clevers; Jeroen den Hertog (Scientific Reports)
Abstract Pseudomonas aeruginosa is a Gram-negative bacterium that is notorious for airway infections in cystic fibrosis (CF) subjects. Bacterial quorum sensing (QS) coordinates virulence factor expression and biofilm formation at population level. Better understanding of QS in the bacterium-host interaction is required. Here, we set up a new P. aeruginosa infection model, using 2D upper airway nasal organoids that were derived from 3D organoids. Using dual RNA-sequencing, we dissected the interaction between organoid epithelial cells and WT or QS-mutant P. aeruginosa strains. Since only a single healthy individual and a single CF subject were used as donors for the organoids, conclusions about CF-specific effects could not be deduced. However, P. aeruginosa induced epithelial inflammation, whereas QS signaling did not affect the epithelial airway cells. Conversely, the epithelium influenced infection-related processes of P. aeruginosa, including QS-mediated regulation. Comparison of our model with samples from the airways of CF subjects indicated that our model recapitulates important aspects of infection in vivo. Hence, the 2D airway organoid infection model is relevant and may help to reduce the future burden of P. aeruginosa infections in CF.